2006
DOI: 10.1152/ajprenal.00032.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibition normalizes arterial blood pressure in CYP1A1-REN2 transgenic rats with inducible ANG II-dependent malignant hypertension

Abstract: The present study was performed to determine the effects of cyclooxygenase (COX)-1 and COX-2 inhibition on blood pressure and renal hemodynamics in transgenic rats with inducible malignant hypertension [strain name: TGR(Cyp1a1Ren2)]. Male Cyp1a1-Ren2 rats (n = 7) were fed a normal diet containing the aryl hydrocarbon, indole-3-carbinol (I3C; 0.3%), for 6-9 days to induce malignant hypertension. Mean arterial pressure (MAP) and renal hemodynamics were measured in pentobarbital sodium-anesthetized Cyp1a1-Ren2 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 56 publications
12
34
0
Order By: Relevance
“…We observed that COX-2 inhibition does not elicit significant alterations of RPF and GFR under NS conditions. This finding is consistent with previous in vivo studies under NS conditions that have not demonstrated a discernible consequence of acutely attenuated prostaglandin biosynthesis on renal hemodynamics (11,26,30). Furthermore, afferent arteriolar diameters of juxtamedullary nephrons in NS rats were not changed by COX-2 inhibition with NS-398 (16).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that COX-2 inhibition does not elicit significant alterations of RPF and GFR under NS conditions. This finding is consistent with previous in vivo studies under NS conditions that have not demonstrated a discernible consequence of acutely attenuated prostaglandin biosynthesis on renal hemodynamics (11,26,30). Furthermore, afferent arteriolar diameters of juxtamedullary nephrons in NS rats were not changed by COX-2 inhibition with NS-398 (16).…”
Section: Discussionsupporting
confidence: 92%
“…During elevated intrarenal ANG II, the addition of meclofenamate, a nonselective COX inhibitor, augmented nimesulide-mediated reductions in blood pressure but did not alter nimesulide-induced reductions in renal vascular resistances, GFR, or RPF (26). Also, in studies using selective COX-1 (genetic deletion and pharmacological) inhibition, COX-1-augmented ANG II increases in systemic resistances were not apparent in the vascular resistances that influence CBF or MBF (29).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Accordingly, this model allows induction of ANG II-dependent hypertension of graded severity using a benign and naturally occurring dietary supplement without the need for surgical intervention, dietary salt manipulation, or the administration of steroids (23,27). In essence, the Cyp1a1-Ren2 transgenic rat model is particularly advantageous because of the ease and reproducibility of genetically clamping expression of the Ren2 gene and inducing increases in plasma renin activity, plasma and intrarenal ANG II levels, and hypertension of graded severity (22,27,28,31,32).We have demonstrated that at a dose of 0.3% (wt/wt), chronic dietary administration of I3C induces malignant hypertension in Cyp1a1-Ren2 transgenic rats (27,28,31,32). Malignant hypertension is a severe form of hypertension characterized by rapidly increasing blood pressure, pressure diuresis and natriuresis, severe renal vasoconstriction and ischemia, activation of the renin-angiotensin system, microangiopathy, hemolytic anemia, and development of retinopathy (23,47,48).…”
mentioning
confidence: 99%
“…We have demonstrated that at a dose of 0.3% (wt/wt), chronic dietary administration of I3C induces malignant hypertension in Cyp1a1-Ren2 transgenic rats (27,28,31,32). Malignant hypertension is a severe form of hypertension characterized by rapidly increasing blood pressure, pressure diuresis and natriuresis, severe renal vasoconstriction and ischemia, activation of the renin-angiotensin system, microangiopathy, hemolytic anemia, and development of retinopathy (23,47,48).…”
mentioning
confidence: 99%